Zidovudine-poly (L-lactic acid) solid dispersions with improved intestinal permeability prepared by supercritical antisolvent process - Yoshida, Valquiria M. H. [UNESP]; Balcao, Victor M.; Vila, Marta M. D. C.; Oliveira Junior, Jose M.; Aranha, Norberto; Chaud, Marco V.; Gremiao, Maria P. D. [UNESP] (Wiley-Blackwell, 2015)
A supercritical antisolvent (SAS) process for obtaining zidovudine-poly(l-lactic acid) (PLLA) solid dispersions (SDs) was used to attain a better intestinal permeation of this drug. A 3(2) factorial design was used, having as independent variables the ratio 3-azido-23-dideoxythymidine (AZT)-PLLA and temperature/pressure conditions, as dependent variables the process yield and particle macroscopic morphology. AZT-PLLA production batches were carried out by the SAS process, and the resulting products evaluated via scanning electron microscope, X-ray diffraction, differential scanning calorimetry, and Fourier transform infrared analyses. From the nine possible combinations of tests performed experimentally, only one combination did not produced a solid. The L3 batch of SD, produced with 1:2 (AZT-PLLA) ratio, resulted in a 91.54% yield, with 40% AZT content. Intestinal permeability studies using the AZT-PLLA from L3 batch led to an AZT permeability of approximately 9.87%, which was higher than that of pure AZT (approximate to 3.84%). AZT remained in crystalline form, whereas PLLA remained in semicrystalline form. AZT release is controlled by a diffusion mechanism. It has been demonstrated that it is possible to use PLLA carrier and SAS process to obtain SD, in a single step. (c) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1691-1700, 2015
Keywords: Supercritical antisolvent process; Supercritical fluids; Zidovudine; Poly (l-lactic acid); Solid dispersion; Oral absorption; Gastrointestinal transit; Everted rat intestinal sacs; Permeability